Adaptasi Galur dan Varietas Gandum (Triticum aestivum L.) di Dataran Tinggi Padang Sidimpuan Sumatera Utara - Muhammad Nizar Hanafiah Nasution; Rasmita Adelina Harahap; Amin Nur (AGRIUM: Jurnal Ilmu Pertanian, 2019)
Wheat adaptation is required in the complex environment especially in the lowland.The purpose of this research is to see growth and the production of different strains and the varieties of wheat in Padang Sidimpuan Angkola Julu with an altitude 700 m above sea level from. The research was being conducted with the course of this experiment quantitative data a shelf on which were (Random Design Group) with 15 treatment wheat and 3 group.Strains and varieties of wheat impact on each variable respons, wheat most adaptive is strain O/HP-92-A1-1-3